2019
DOI: 10.3201/eid2503.181003
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Border Movement of Highly Drug-Resistant Mycobacterium tuberculosis from Papua New Guinea to Australia through Torres Strait Protected Zone, 2010–2015

Abstract: In this retrospective study, we used whole-genome sequencing (WGS) to delineate transmission dynamics, characterize drug-resistance markers, and identify risk factors of transmission among Papua New Guinea residents of the Torres Strait Protected Zone (TSPZ) who had tuberculosis diagnoses during 2010–2015. Of 117 isolates collected, we could acquire WGS data for 100; 79 were Beijing sublineage 2.2.1.1, which was associated with active transmission (odds ratio 6.190, 95% CI 2.221–18.077). Strains were distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 35 publications
0
24
0
Order By: Relevance
“…A strategic framework for cross-border TB control programmeming was developed for highly mobile populations [ 59 ], but the initiative was not materialized to handle patients requesting cross-border referral that resulted in treatment discontinuations. Thus, the risk of drug resistance due to treatment discontinuation and exchange of resistant strains would be alarming among migratory patients in the setting [ 60 ]. This implies the need for founding cross-border collaboration platforms in the region.…”
Section: Discussionmentioning
confidence: 99%
“…A strategic framework for cross-border TB control programmeming was developed for highly mobile populations [ 59 ], but the initiative was not materialized to handle patients requesting cross-border referral that resulted in treatment discontinuations. Thus, the risk of drug resistance due to treatment discontinuation and exchange of resistant strains would be alarming among migratory patients in the setting [ 60 ]. This implies the need for founding cross-border collaboration platforms in the region.…”
Section: Discussionmentioning
confidence: 99%
“…In Vietnam, Holt et al reported that, although the Beijing strains accounted for 58% of the total study sample, they constituted 70% of all clustered strains (21). In Papua New Guinea, Bainomugisa et al found that 82% of isolates with Beijing strains were found in clusters, compared with 43% of isolates with strains from other lineages (37). In China, Yang et al reported that the proportions of clustering were 34% for Beijing and 18% for non-Beijing strains (38).…”
Section: Discussionmentioning
confidence: 99%
“…We estimated the molecular clock phylogeny and mutation rate of lineage 1 isolates using a previously described method [ 10, 19 ]. The mutation rate was estimated to be 0.56 SNPs/genome/year [95 % highest posterior density (HPD) 0.23–0.79], similar to other published studies [ 27, 33, 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Molecular dating of sub-lineage 1.2 isolates using beast 1.8.2 [ 24 ] was performed as previously described [ 10 ]. We assessed the temporal signal in a neighbour-joined tree (K80 substitution model) by undertaking regression of the root-to-tip distance over time using TempEst v1.5.…”
Section: Methodsmentioning
confidence: 99%